Soft Soil Stabilisation Via Vertical Drainage with Minimal Site Disturbance: A Case Study at Cameron Highlands - Chong, Wei-An; Chan, Chee-Ming; Tan, Poi-Cheong; Sani, Salina; Yahya, Nur Faezah; A. Rahman, Noor Khazanah (International Journal of Integrated Engineering, 2025)
Vertical drains are often adopted to improve poor ground conditions by accelerating consolidation process of soils. This paper describes a case study utilising this technique to stabilise soft soils in Cameron Highlands. This method involves the installation of vertical drains with embankment and the permeable characteristic of the prefabricated vertical drains. The details of the vertical drain design and the construction of the project were also studied. In addition, site disturbance control measures and on-site monitoring methods should be implemented to manage the impact of the construction. In summary, this paper indicates the application of the vertical drain to stabilise high-rise soft soils and recommends the construction process to provide a reference for sites with similar locations or height.